Automation of a kitting station at Scania Luleå - Hansson, Emma (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2023)
Scania Luleå is a part of Scania CV that has approximately 50 000 employees in 100 different country´s and is a manufacturer of trucks, buses and power solutions. At Scania Luleå; side beams, chassi details and rear axle housings are manufactured. This master´s thesis was focused on a kitting station for rear axle housing production. The purpose of this master thesis was to do a feasibility study and an investment justification for an automatic kitting station for this production line. The goal was to develop one or more concepts for an automatic kitting station, five key factors was taken in to account: reliability, cost of cell, cell size, need for operators, equipment and one-piece flow. The scope for the project excluded transport to and from the kitting area, as well as future components or products. This was obtained through different methods of concept generation, such as brainstorming and brainwriting, resulting in 12 different concepts, with concepts ranging from operators preforming the main work to other concepts that were fully automated. To evaluate the concepts, some calculations were made on the needs of the equipment, the cost both for investments and installations but also for the need for operators. After evaluation 2 concepts remained one with operators and one with robots. A simulation was made to get a better understanding of the concept with robots and some detailed calculations was made for the concept with an operator. The purpose was that the simulation for the concept with one operator would take too long time to perform and would not give a better result or understanding than basic calculations. Finally, two recommendations were made; one short term and the other one long term concept.